2015
DOI: 10.1080/0952813x.2015.1024492
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of spatio-temporal patterns from location-based social networks

Abstract: Location Based Social Networks (LBSN) like Twitter or Instagram are a good source for user spatio-temporal behavior. These networks collect data from users in such a way that they can be seen as a set of collective and distributed sensors of a geographical area. A low rate sampling of user's location information can be obtained during large intervals of time that can be used to discover complex patterns, including mobility profiles, points of interest or unusual events. These patterns can be used as the elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
1
12
0
1
Order By: Relevance
“…Moreover, the spatial distribution of our research also coincides with the pattern of tourist distribution in some other cities, as described in the literature review. This result is similar to the conclusion of Béjar et al (2014) which utilizes Instagram data, a finding that indicates different datasets may be comparable, as long as the volume of the dataset is substantial.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, the spatial distribution of our research also coincides with the pattern of tourist distribution in some other cities, as described in the literature review. This result is similar to the conclusion of Béjar et al (2014) which utilizes Instagram data, a finding that indicates different datasets may be comparable, as long as the volume of the dataset is substantial.…”
Section: Discussionsupporting
confidence: 83%
“…Hasnat et al (2018) described tourist movements as clustered around tourist attractions based on Twitter data in Florida. Béjar et al (2014) extracted the spatial-temporal characteristics of Twitter and Instagram users in Barcelona; they found that the main tourist attractions were important connecting nodes in both datasets, though their study did not distinguish tourist users from locals. Kádár (2014) concluded that the majority of geo-tagged images generated from Flickr tourist users were gathered around tourist attractions or landmarks in Budapest.…”
Section: Study Of Tourist Activities Based On Lbsn Datamentioning
confidence: 99%
“…Actualmente, el incremento en el uso de dispositivos móviles ha permitido obtener datos suficientes en otros ámbitos y extender este tipo de estudios también a ciudades de menor tamaño -entre 50 y 100 mil habitantes- (Morstatter et al, 2013;Leontidou et al, 2007;Lansley y Longley, 2016). También, el auge de otras redes sociales -como pueden ser Foursquare, Google Places o Pinterest-, ha permitido ampliar los temas de estudio (Martí, Serrano-Estrada y Nolasco-Cirugeda, 2017;De Vries et al, 2013;Byers, Proserpio y Zervas, 2016;Béjar et al, 2016; García-Palomares, Gutierrez y Mínguez, 2015).…”
Section: Los Datos Generados En Redes Sociales Como Fuente Para El Esunclassified
“…Moreover, considering the findings of previous studies [29,33,34], we also examine the time-related characteristics of calling activity to reveal the dynamics more clearly. Commonly, daily patterns and intraday patterns are examined to discover time-related characteristics of human behavior, such as calling activity between individuals [43], web browsing activity [35], user activity in virtual worlds [36], Wikipedia editorial activity [37], activity on Twitter and Instagram [38], and spatio-temporal properties of cities in Spain [44]. Motivated by these studies, we apply the k-means method and statistical analysis to examine daily patterns and intraday patterns.…”
Section: Introductionmentioning
confidence: 99%